2016
DOI: 10.5953/jmjh.2016.23.2.105
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of SBAR Reports on Communication Clarity and Nurse-Physician Collaborative Relationships: A One Group Pretest-Posttest Design

Abstract: Purpose: The purpose of this study was to investigate the effect of Situation-Background-Assessment-Recommendation (SBAR) reports on communication clarity and nurse-physician collaborative relationships. Methods: SBAR forms in one group were measured at baseline, at 2 weeks, and at 4 weeks postintervention. The subjects were 30 nurses who worked in a general ward of a general hospital in B city, Korea. A 45-minute SBAR education was provided to all subjects. Data was collected between September to October 2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…In our study, the element of SBAR least practiced during communications with physicians in clinical deterioration was the recommendation, with the highest practice of situation, followed by background and assessment. A study that investigated the effects of SBAR reporting on a collaborative relationship with physicians among ward nurses in a tertiary hospital also showed that nurses felt awkward and uncomfortable presenting recommendations to a physician and were hesitant [27]. Narayan [15] also reported that nurses nd it challenging to present opinions about the following steps to a physician despite knowing what went wrong and the best solution.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…In our study, the element of SBAR least practiced during communications with physicians in clinical deterioration was the recommendation, with the highest practice of situation, followed by background and assessment. A study that investigated the effects of SBAR reporting on a collaborative relationship with physicians among ward nurses in a tertiary hospital also showed that nurses felt awkward and uncomfortable presenting recommendations to a physician and were hesitant [27]. Narayan [15] also reported that nurses nd it challenging to present opinions about the following steps to a physician despite knowing what went wrong and the best solution.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…A study that investigated the effects of SBAR reporting on a collaborative relationship with physicians among ward nurses in a tertiary hospital also showed that nurses felt awkward and uncomfortable presenting recommendations to a physician and were hesitant. [ 27 ] Narayan [ 15 ] also reported that nurses find it challenging to present opinions about the following steps to a physician despite knowing what went wrong and the best solution. After detecting clinical deterioration, presenting a precise suggestion of what is required could help physicians give immediate and most suitable orders.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…This finding was consistent with the results of previous studies that showed inexperienced nursing students complained of considerable difficulty and communicated inadequately and unclearly in a series of situations where they must judge and analyze patients’ problems based on theoretical knowledge and communicate with other medical staff [ 35 ]. Kim et al [ 36 ] also reported that nurses were reluctant to make suggestions to doctors because they felt awkward and uncomfortable. This attitude could be the result of the hierarchical culture of hospitals, particularly in Korean society.…”
Section: Discussionmentioning
confidence: 99%